An Update on Wrong-Site Spine Surgery - DeVine, John G. (Global Spine J, 2020)
STUDY DESIGN: Broad narrative review of current literature and adverse event databases. OBJECTIVE: The aim of this review is to report the current state of wrong-site spine surgery (WSSS), whether the Universal Protocol has affected the rate, and the current trends regarding WSSS. METHODS: An updated review of the current literature on WSSS, the Joint Commission sentinel event statistics database, and other state adverse event statistics database were performed. RESULTS: WSSS is an adverse event that remains a potentially devastating problem, and although the incidence is difficult to determine, the rate is low. However, given the potential consequences for the patient as well as the surgeon, WSSS remains an event that continues to be reported alarmingly as often as before the implementation of the Universal Protocol. CONCLUSIONS: A systems-based approach like the Universal Protocol should be effective in preventing wrong-patient, wrong-procedure, and wrong-sided surgeries if the established protocol is implemented and followed consistently within a given institution. However, wrong-level surgery can still occur after successful completion of the Universal Protocol. The surgeon is the sole provider who can establish the correct vertebral level during the operation, and therefore, it is imperative that the surgeon design and implement a patient-specific protocol to ensure that the appropriate level is identified during the operation.